Revitalization of Cracked Flexural Members Using Retrofitting and Synthetic Wrapping. (2017) - Tudjono, Sri; Lie, Han Ay; Gan, Buntara Sthenly
Abstract: The modification of the Indonesia earthquake code SNI 2002 to SNI 2012 resulted in a significantly higher performance demand. The basics of these amendments lay in the re-zoning of earthquake maps, and the consideration of the earthquake influence to gravity loads. Members designed based on the SNI 2002 most likely will result in failure under future earthquakes. A reinforcement method based on the ACI 440 provision was conducted on cracked flexural members. The tensile reinforcement of these members has yielded and was neglected in the design. The tensile strains and stresses were further carried by the synthetic wraps applied to the tensile concrete fibers. The shear capacity of the member was enhanced by confinement of the member using the same synthetic wrap. Prior to wrap application, the members were straightened and retrofitted with an epoxy resin injection. The member was tested using a one-point-loading system to simulate a maximum bending moment in combination with maximum shear forces. The load-displacement responses and the ultimate load carrying capacity under monotonic incremental loading were recorded. It was found that this method will provide a solution for revitalization of cracked members in bending, and offer a solution to the design code alterations.